Adverse Effects of Pharmacologic Treatments of Major Depression in Older Adults - Sobieraj, Diana M. (2019)
OBJECTIVES To assess adverse effects of pharmacologic antidepressants for treatment of major depressive disorder (MDD) in adults 65 years of age or older. DESIGN Systematic review and meta‐analysis. SETTING Specialist or generalist outpatient setting, rehabilitation facility, and nursing facilities. PARTICIPANTS Persons 65 years and older with MDD. INTERVENTION Selective serotonin reuptake inhibitors (SSRIs), serotonin norepinephrine reuptake inhibitors (SNRIs), bupropion, mirtazapine, trazodone, vilazodone, or vortioxetine compared with another antidepressant, placebo, or nonpharmacologic therapy. MEASUREMENTS Adverse events, arrhythmias, cognitive impairment, falls, fractures, hospitalization, mortality, QTc prolongation, serious adverse events, and withdrawals due to adverse events.